Silage additives - Bolsen, K.; Ilg, H. (Kansas State University. Agricultural Experiment Station, 2011)
Six commercial silage additives were evaluated in five trials with corn, forage sorghum, and alfalfa. In general, each additive improved the silage in at least one of four criteria we used for the comparisons: ensiling temperature, silage dry matter (DM) loss during fermentation, cattle performance, and silage stability in air. The additives lowered ensiling temperatures during the first week by about 5F (range, 2.7 to 9.9F). Additives consistently reduced DM lost during fermentation. Loss from five control silages averaged 10.0% compared with 4.7% from nine silages with additives. No silage additive significantly affected rate of gain or silage intake in the four trials with growing cattle. In three of six comparisons, additives increased feed efficiency slightly; but in the other three, additives decreased feed efficiency slightly. In five comparisons, additives increased aerobic stability of silages on feedout, but again in the other five, additives decreased silage aerobic stability on feedout.
Keywords: Beef; Silage additives; Fermentation; Dry matter